(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the disease patterns of patients receiving examination and treatment at the Department of Traditional Medicine of Cam Khe District Health Center during the period 2022–2024, and to assess the current status of healthcare delivery using Traditional Medicine and Traditional Medicine integrated with Modern Medicine at this department in 2024. Based on the International Classification of Diseases, 10th Revision (ICD-10), disease groups managed at the Department of Traditional Medicine and Rehabilitation, Cam Khe District Health Center, Phu Tho Province in 2024 were mainly classified under Chapters VI, IX, and XIII, with a predominance of Chapter XIII conditions (diseases of the musculoskeletal system and connective tissue). The disease pattern was largely dominated by noncommunicable diseases (NCDs), with musculoskeletal and connective tissue disorders accounting for the highest proportion. Conclusion: The disease pattern at the Department of Traditional Medicine and Rehabilitation of Cam Khe District Health Center reflects a substantial burden of chronic musculoskeletal and neurological conditions among the elderly population, in line with the national epidemiological transition as defined by the World Health Organization. The current treatment practice demonstrates that the integration of Traditional Medicine and Modern Medicine has been effectively implemented, optimizing the use of non-pharmacological interventions and reinforcing the essential role of Traditional Medicine within district-level primary healthcare services.